The use of commitment techniques to support weight loss maintenance in obese adolescents. Issue 11 (1st November 2016) - Kulendran, Myutan; King, Dominic; Schmidtke, Kelly Ann; Curtis, Claire; Gately, Paul; Darzi, Ara; Vlaev, Ivo
Abstract : Objectives: Obesity is a rising problem in adolescents related to unhealthy behaviours. Commitment devises are one type of behavioural intervention that may help people change their behaviours. The current pilot trial tests whether commitment devices delivered via text message help adolescents maintain their recent weight loss. Methods: During a 12-week pilot trial, adolescents who attended a weight loss camp were randomly assigned to either received text messages that contained only information, i.e. advice, about weight loss management ( n = 13) or asked for them to commit to following the same advise ( n = 14). Results: The BMI of the adolescents in the commitment group did not change. In contrast, the BMI of adolescents in the information group increased. A linear regression revealed that group was a significant predictor of BMI change. A logistic regression revealed that adolescents in the information group were nearly eight times more likely to regain weight than those in the commitment group. Conclusions: This is the first study with adolescents to show weight maintenance using a commitment device. The results suggest that commitment devices can help adolescents maintain their recent weight loss.